A dragon's guide to the care and feeding of humans - Yep, Laurence, 1948-; Ryder, Joanne (Crown Books for Young Readers, 2015)
Crusty dragon Miss Drake's new pet human, precocious ten-year-old Winnie, not only thinks Miss Drake is her pet, she accidentally brings to life her "sketchlings" of mysterious and fantastic creatures hidden in San Francisco, causing mayhem among its residents.